THE PATTERN AND TREND OF FATWA RELATED TO HALAL CONSUMPTION LAW IN NEGARA BRUNEI DARUSSALAM: ANALYZING HISTORICAL DATA OF PREVIOUS FATWAS ISSUED - Nurdeng Deuraseh; Raihana Mohd Raffi; Amalina Roslan; Rahmadi Indra Tektona (Diponegoro Law Review, 2022)
Fatwa has been issued in Brunei since the appointment of the first state mufti in 1961, releasing a total of 1525 fatwas throughout his service until 1994. This effort is being continued by Brunei’s current state of mufti since 1994. Various categories of fatwas have been issued and compiled in a series of books as public references. Halal consumption especially in food has been a continuing phenomenon among Muslims. Analyzing previous fatwas can help to interpret patterns or trends for the benefit of future studies or matters of improvement. This study aims to achieve those objectives by analyzing historical data, focusing on fatwas issued about halal consumption. The document analysis method was used to look through fatwas issued from 1994 to 2015 It was found that 6 different areas such as alcohol, ingredients, animal slaughter, food handling, non-muslim involvement, and halal status of the animal. Past fatwas have also shown the importance of laboratory analysis in deducing fatwa. The effect of law implementation can also be seen in this analysis.